Challenges Faced By Child Protection Officers in the Rehabilitation of Destitute Children: Case Study of Child Protection and Welfare Bureau, Punjab - Mariam Zahoor Khan; Aleena Bashir (`, 2025)
The case study is on the Child Protection and Welfare Bureau (CP&WB) in Punjab, Pakistan, as it confronts the difficulties of rehabilitating impoverished and neglected children. Punjab, as the most populous province in Pakistan, has distinct socio-economic and cultural variables that have an influence on the welfare of its children. The CP&WB, established to tackle such matters, plays a key role in safeguarding and rehabilitating children facing challenging circumstances. In-depth exploration of the rehabilitation and protection of children by the Child Protection and Welfare Bureau (CPWB) and the challenges faced by its core team. To achieve this, the researcher opted for the purposive sample technique for the type of population that was available and the study objectives and questions needed to access the population in the study. Interviews were conducted under data saturation, where the researcher realized that there was no new information to be obtained from the interviews. This was done according to the level of saturation in the study, with 45 participants comprising of 15 children and 30 practitioners. Altogether, the analyzed data show that participants share a rather favorable attitude toward safety within the CPB through appreciation of staff assistance and overall trust in care. The interactions between the staff and CPB seem to be generally positive in terms of the reception the organization has received, and some difficulties were mentioned in the areas of either being heard or understood. The answers concerning observing situations connected with abuse or neglect differ, stressing the action of a staff member as the important factor. Lack of equal training on rights, desire substantiation, and proposal to improve CPB services stresses the necessity of complete teaching and augmentation. The implementation of all the listed critical success factors is based on the four crosscutting themes: Communication, empowering, training, and individual support means that the CPB requires a supportive, transparent, and friendly environment that attends to individual and structural GAP children in protection. Keywords: Child Protection, Rehabilitation Destitute Children, Child Protection Officers, Welfare Bureau (CPWB)